4
$\begingroup$

Evaluate $$\frac{\prod_{i=1}^n[(2i-1)^4+ 1/4]}{\prod_{i=1}^n[(2i)^4+ 1/4]}$$

First I thought I would multiply both the numerator and the denominator by the denominator itself. Now, I am unable to evaluate the series. I would appreciate innovative ideas to evaluate this product.

$\endgroup$
  • 1
    $\begingroup$ Please try to make the titles of your questions more informative. For example, Why does $a<b$ imply $a+c<b+c$? is much more useful for other users than A question about inequality. From How can I ask a good question?: Make your title as descriptive as possible. In many cases one can actually phrase the title as the question, at least in such a way so as to be comprehensible to an expert reader. You can find more tips for choosing a good title here. $\endgroup$ – Shaun Mar 30 at 19:24
7
$\begingroup$

We shall slightly rewrite the task: $$ \frac{\prod_{i=1}^n[(2i-1)^4+ 1/4]}{\prod_{i=1}^n[(2i)^4+ 1/4]} = \prod_{i=1}^n\frac{[(2i-1)^4+ 1/4]}{[(2i)^4+ 1/4]} $$

First note the equality $$ x^4 + \frac14 = (x^2 + x + \frac12)(x^2 - x + \frac12) $$ So a term in the product gives $$ \frac{(2i-1)^4+ 1/4}{(2i)^4+ 1/4} = \frac{[(2i-1)^2+(2i-1)+ 1/2][(2i-1)^2-(2i-1)+ 1/2]}{[(2i)^2+2i+ 1/2][(2i)^2-2i+ 1/2]} $$ Now we multiply out and get $$ (2i-1)^2+(2i-1)+\dfrac{1}{2}=(2i)^2-4i+1+2i-1+\dfrac{1}{2}=(2i)^2-(2i)+\dfrac{1}{2} $$ which makes the term in the product $$ \frac{(2i-1)^4+ 1/4}{(2i)^4+ 1/4} = \frac{(2i-1)^2-(2i-1)+ 1/2}{(2i)^2+2i+ 1/2} $$ Trying to reduce the numerator from $(2i-1)$ to $(2i-2)$ we observe that $$ (2i-2)^2+(2i-2)+\frac{1}{2}=(2i)^2-8i+4+2i-2+\frac{1}{2}=(2i-1)^2-(2i-1)+\frac{1}{2} $$ which makes the term in the product $$ \frac{(2i-1)^4+ 1/4}{(2i)^4+ 1/4} = \frac{(2i-2)^2+(2i-2)+\frac{1}{2}}{(2i)^2+2i+ 1/2}= \frac{(2(i-1))^2+2(i-1)+\frac{1}{2}}{(2i)^2+2i+ 1/2} $$ Now we can perform the product, since by telescoping all "inner" numerators and denominators cancel: $$ \prod_{i=1}^n\frac{[(2i-1)^4+ 1/4]}{[(2i)^4+ 1/4]} = \prod_{i=1}^n \frac{(2(i-1))^2+2(i-1)+\frac{1}{2}}{(2i)^2+2i+ 1/2} \\ = \frac{(2\cdot 1-2)^2+(2\cdot 1-2)+\frac{1}{2}}{(2\cdot n)^2+2\cdot n+ 1/2} = \frac{1}{8 n^2+ 4 n+ 1} $$ This completes the evaluation. $\qquad \Box$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.